Skeletal muscle oxygenation and regional blood volume during incremental limb loading in interstitial lung disease. Issue 1 (27th January 2020) - Wickerson, Lisa; Mathur, Sunita; Brooks, Dina; Bonetti, L.V.; Singer, Lianne G.; Granton, John; Reid, W. Darlene
Introduction: Individuals with interstitial lung disease (ILD) exhibit reduced exercise capacity and exertional hypoxaemia. The role of peripheral (muscle) limitation to exercise tolerance in ILD is not well studied to date. Methods: A prospective cross-sectional study examined skeletal muscle oxygen saturation ( S mO2 ) and regional blood volume of the knee extensors and elbow flexors during incremental limb loading in healthy people and people with varying severity of ILD. Isotonic concentric exercise was performed on an isokinetic dynamometer. S mO2 and regional blood volume were measured by near-infrared spectroscopy over the vastus lateralis and biceps. Results: Thirteen people who were dependent on oxygen, candidates for lung transplant and with severe ILD (forced vital capacity (FVC) 59±20% predicted), 10 people who were not oxygen dependent with mild ILD (FVC 81±17% predicted) and 13 healthy people (FVC 101±14% predicted) were included. Total haemoglobin, a marker of regional blood volume, was lower at task failure in the knee extensors in participants with severe ILD compared to healthy participants (p=0.05). At task failure for both knee-extensor loading and elbow-flexor loading, S mO2 was decreased to similar levels across all groups, but occurred at lower total workloads in the ILD groups (all p<0.01). Conclusions: Overall, people with severe ILD had lower levels of total work and experienced less increase in blood volume in the knee extensors after knee-extensor loading compared to healthy people. Peripheral muscle dysfunction in severe ILD may have contributed to muscle deoxygenation at lower workloads. Muscle deoxygenation occurs at a lower level of lower-limb incremental loading in lung transplant candidates with interstitial lung disease and regional blood volume is attenuated compared to healthy persons http://bit.ly/34z0Qtw